PENGARUH INTERVAL WAKTU PEMBERIAN AIR TERHADAP PRODUKTIVITAS TANAMAN TOMAT DI LAHAN KERING DATARAN RENDAH PADA MUSIM KEMARAU - Sy, Erie Maulana; Idrus, Muhammad (Politeknik Negeri Lampung., 2010)
The research was conducted in research station Polytechnic of Lampung, started the April from November 2009. The experiment was conducted in randomized completely block design with 3 replications. The treatments irrigation interval water gift time consist of 4, 6, 8, and 10 days. The parameters that were (1) tall plants, (2) fruit total formed, (3) production, (4) irrigation water gift total, and (5) water productivity. The data obtained to be analysed use anova, with BNT test for the mean of treatments value with level 0.05. The result of research indicate that are irrigation interval of 8 days in tomato plants cultivar Mutiara at dry season of lowland gave economical benefit per unit of water and can be conserved 47% irrigation water with production 1.28 kg.plants-1 (28.33 ton.ha-1). Keywords : Irrigation interval, tomato production, dry season, lowland